Social isolation, homebound status, and race among older adults: Findings from the National Health and Aging Trends Study (2011–2019). Issue 7 (12th April 2022) - Cudjoe, Thomas K. M.; Prichett, Laura; Szanton, Sarah L.; Roberts Lavigne, Laken C.; Thorpe, Roland J.
Abstract: Background: Multiple factors may influence the risk of being homebound, including social isolation and race. This study examines the relationship between social isolation and homebound status by race over 9 years in a sample of adults. Methods: Utilizing a representative sample of 7788 Medicare beneficiaries aged 65+ from 2011–2019, we assessed the odds of becoming homebound by social isolation. We defined social isolation as the objective lack of contact with others. We defined severe social isolation as scoring a 0 or 1 on a social connection scale from 0 to 4. Homebound status was defined as never leaving home or only leaving home with difficulty. Utilizing a multivariate Cox proportional hazards model adjusting for age, gender, marital status, income, and education, we examined the association between social isolation at baseline and becoming homebound during the study in those who were not initially homebound. Results: Older adults in this study were on average 78 years old. Overall, most were white (69%), female (56.3%), and married (57.8%) and reported that they had a college education or higher (43.9%). Also, at baseline, approximately 25% of study participants were socially isolated, 21% were homebound, and 6.3% were homebound and socially isolated or severely socially isolated. Homebound status at baseline varied by race: Black, 23.9% and white, 16.6% ( p < 0.0001). After 9 years, socially isolated black (hazard risk ratio, HRR 1.35, 95% confidence interval CI [1.05, 1.73], p < 0.05) and white (HRR 1.25, 95% CI [1.09, 1.42], p < 0.01) older adults were at higher risk of becoming homebound. Conclusion: Socially isolated black and white adults are more likely to be homebound at baseline and become homebound over time. Further research is needed to determine whether community‐based strategies and policies that identify and address social isolation reduce homebound status among community‐dwelling older adults.